History of the magazine "Litoral": letters & calligraphy (II) (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2021)
In the last 100 years of its history, Litoral has received a vast quantity of material for potential publication. In the beginning was the letter and since Litoral was born in 1968 again with José María Amado as director until now with Lorenzo Saval, we have cataloged a great variety of handwritten letters, epistolary material and artists’ personal documents written with a calligraphy is sometimes close to an art piece. If we have a look at the list of collaborators we will find the most popular artists from poetry, music, painting and typography, of contemporary Spain. This work is the second from a series dedicated to the same topic.
Keywords: Litoral. Poetry magazine, Art & Thought; Epistolary; Letters; Calligraphy; 27th generation